Heterotopic grafting sites can be useful in producing oocytes for in vitro Fertilization, therefore, maximising the oocyte yield from the graft by gonadotrophin stimulation would be advantageous. The aim of this study was to investigate the number and quality of oocytes collected from heterotopic autografted ovary after Pregnant Mare Serum Gonadothropin (PMSG) induction. Graft recipients were treated either with or without PMSG stimulation 48 hours prior to graft collection. Ovarian tissue from - . NURBARIAH; ITA DJUWITA; KUSDIANTORO MOHAMAD; IMAN SUPRIATNA (HAYATI Journal of Biosciences, 2011)
Heterotopic grafting sites can be useful in producing oocytes for in vitro Fertilization, therefore, maximising the oocyte yield from the graft by gonadotrophin stimulation would be advantageous. The aim of this study was to investigate the number and quality of oocytes collected from heterotopic autografted ovary after Pregnant Mare Serum Gonadothropin (PMSG) induction. Graft recipients were treated either with or without PMSG stimulation 48 hours prior to graft collection. Ovarian tissue from four weeks old mice (DDY strain) were autotransplanted under the kidney capsule of the same ovariectomized mice and the oocytes were collected 21 days after autotransplantation. The results showed that the average number of oocytes collected from autografted ovaries without PMSG induction were 9.0. + 2.8 not significantly different with those received PMSG induction, 10.9 + 5.1. The percentage of matured and fertilized oocytes and the developed embryos from the autografted ovaries without PMSG induction were 52.4, 33.4, and 26.0%, respectively not significantly different with those received PMSG induction, 53.2, 35.1, and 29.9%, respectively. The number of oocytes and the capacity to matured, fertilized and developed were significantly lower (P < 0.05) compared to the superovulated nongrafted (control) ovaries. In conclusion, PMSG induction on the graft recipients did not significantly increase oocytes yield from grafted heterotopic ovaries. The number and quality of oocytes produced from the autografted ovaries were lower than the superovulated nongrafted ovaries, but still can be used for in vitro embryo production after sequential in vitro maturation and fertilization.